Історія інтродукції роду Calluna Salisb. у Національному ботанічному саду імені М.М. Гришка НАН України - Smilyanets, N.M.; Kuznetsova, M.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
The article contains results of research of the archival documents of M.M. Gryshko National Botanical Garden (NBG) of the NAS of Ukraine, relating to the introduction of common heather (Calluna vulgaris (L.) Hull), since 1938. It was found that in the NBG for the first time heather plants were obtained in 1946 from Germany, but in the subsequent inventory documents they are not mentioned. Further, data on the presence of heather in the collections are fixed periodically in inventory registers, the last reference dates back to 1974. After 1979 inventory data were not submitted to the archive, that is why we were not able to trace the presence of common heather in them. Targeted collection of heather varieties began in 2006, "Heather garden" was opened in 2012, where common heather is growing. Also here is the largest in Ukraine collection of varieties of common heather (54 varieties). In "Heather garden" the other plants of the such families as Ericaceae Juss, Magnoliaceae Juss. and Pinaceae Spreng. ex F. Rudolphi are growing. The history of the introduction of heather C. vulgaris in the NBG can be divided into four phases, the last of which (from 2006) is the most productive.